1987
DOI: 10.1172/jci113197
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide protects against acute ischemic renal failure in the rat.

Abstract: Because of its ability to increase glomerular filtration, antagonize the actions of vasoconstrictors, and produce vasodilatation, alpha human atrial natriuretic peptide (a-hANP) was evaluated for its potentially beneficial effects in experimental ischemic renal failure induced by 45-60 min of renal artery occlusion in bilaterally or unilaterally renally intact SpragueDawley rats. After ischemia, a 4-h intrarenal infusion of ahANP restored 14C-inulin clearances in bilaterally and unilaterally intact animals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…ANP also induces redistribution of renal medullary blood flow (Davis and Briggs 1987). Furthermore, ANP has been shown to improve renal function in rats with ischemic acute renal failure by improving renal adenosine triphosphate regeneration after reperfusion (Nakamoto et al 1987), thereby preserving the glomerular filtration rate and thus reducing renal tissue damage (Shaw et al 1987). However, the mechanisms of the renoprotective effects of ANP remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ANP also induces redistribution of renal medullary blood flow (Davis and Briggs 1987). Furthermore, ANP has been shown to improve renal function in rats with ischemic acute renal failure by improving renal adenosine triphosphate regeneration after reperfusion (Nakamoto et al 1987), thereby preserving the glomerular filtration rate and thus reducing renal tissue damage (Shaw et al 1987). However, the mechanisms of the renoprotective effects of ANP remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that cyclic GMP, a second messenger induced by NO, is elaborated by the kidney during IL-2 therapy (68,73,74). It has been shown that atrial natriuretic factor, a peptide with vasodilating and diuretic/natriuretic properties, ameliorates, via cyclic GMP, the severity of acute renal failure (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…The reno-protective effect of ANP during endotoxemia could therefore be traced in the absence of renal nerves, although the improvement in the GFR value was relatively minor, considering the massive pharmacological dose of ANP employed. Recent studies show a therapeutic potential of the ANP for preserving renal function after renal ischemia [8,9]. ANP administration immediately after the ischemic insult significantly improves renal structure and function as assessed by GFR and ATP generation [9,10], the effects of which are not seen with other vasodilators such as acetylcholine [27] and nitroprusside [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show a therapeutic potential of the ANP for preserving renal function after renal ischemia [8,9]. ANP administration immediately after the ischemic insult significantly improves renal structure and function as assessed by GFR and ATP generation [9,10], the effects of which are not seen with other vasodilators such as acetylcholine [27] and nitroprusside [28]. The renal effect of ANP in the renal ischemic injury may be due to an increase in intraglomerular pressure which resulted from a unique combination of preglomerular arteriolar dilatation and efferent constriction [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation